Research of Medieval Heritage of Ganja City Based on Historical Sources - Hasanov, Elnur (Maddah: Journal of Advanced Da'wah Management Research, 2025)
Scientific work deals with the research the cultural heritage of Ganja city on the basis of various manuscripts, different historical documents as the sources in research of the cultural and sociological development during the medieval period. The life and creation of such genius persons as Nizami Ganjavi have been studied based on archival materials, various written sources, historical documents, literary samples for the medieval period on the basis of comparative scientific approach. The purpose of the study is 1) to analyze the role of women in the Akhilik ideology in the works of Nizami Ganjavi, and 2) to analyze the influence of Nizami Ganjavi on Sufi and Akhilik traditions in Ganja. The methods used for this study included historical and comparative research metod, chronological, source method. The research findings show that 1) Nizami Ganjavi portrays women as symbols of strength, wisdom, and love within the Akhilik ideology, promoting gender equality and women’s empowerment in da’wah management. 2) Nizami's contributions to Sufi and Akhilik traditions emphasize courage, justice, and wisdom, providing a framework for da’wah that integrates moral and social values, promotes spiritual growth and social welfare, and addresses contemporary societal challenges.